Coronary artery calcium quantification on first, second and third generation dual source CT: a comparison study - Vonder, Marleen; Haubenreisser, Holger; Meyer, Mathias; Henzler, Thomas (Journal of cardiovascular computed tomography, 2017)
Background: Differences in coronary artery calcium (CAC) quantification of successive CT systems of one vendor could impact results of CAC screening and progression studies. The purpose of this study is to compare CAC quantification between three generations of dual-source computed tomography (DSCT) systems.Methods: Three DSCT generations were used to repeatedly scan an anthropomorphic chest phantom and three inserts. The first and second insert contained 100 small and nine large calcifications, respectively, to determine detectability, and the Agatston and (calibrated) mass score, respectively. A third insert containing a moving artificial coronary artery was used to determine impact of movement on calcium scoring. Data were acquired at 120 kVp, 90 reference mAs with prospective electrocardiographic(ECG)-gating at sequential and high-pitch spiral mode, for respectively first and second/third generation DSCT. Differences and variability in detectability and calcium scores were analyzed. Results: Although noise levels differed (p=<0.002), no differences in detectability were found between the three DSCT generations; median (range) for first, second and third generation were 11 (8), 11 (4) and 12 (2) out of 100 calcifications (p > 0.272). Between second and third generation no difference was found in Agatston score for the large calcification phantom (p > 0.05). The intra-scanner variability and inter-scanner median relative difference ranged for Agatston score from 2.1 to 8.3% and 0.5-12.7% and for mass score from 1.4% to 4.4% and 0.7-5.6%. Overall, intra-scanner variability was lowest for third generation DSCT. Conclusion: The three DSCT generations have similar detectability of calcifications. Median Agatston and mass score differed by no more than 12.7% and 5.6%.